KING'S THE STAND: DWELLING NECROPOLITICS IN PANDEMIC'S LEGACY - Poetri, Maharanny; Salam, Aprinus (University of Kuningan, 2025)
This research examines Stephen King's The Stand through the lens of Achille Mbembe's necropolitics and the pandemic narrative approach, analyzing how the novel portrays a pandemic as a state of siege. The research reveals that the pandemic in The Stand serves not only as a source of fear and societal disruption, highlighting human mortality and the fragility of social structures, but also as a catalyst for necropolitical governance, where sovereignty operates through the control of life and death, utilizing fear to maintain dominance. Utilizing a qualitative methodology focused on character interactions, control mechanisms, and depictions of death, the research demonstrates how the post-pandemic landscape in the novel reflects a slow social and political death, alongside physical demise. Additionally, this work implicates King's negotiation of humanity as an aspiration for peace, effectively neutralizing the pervasive fear of necropolitical implementation during a pandemic, as perceived at the time of the novel's release.